Headscarf (Hijab) at work and dismissal: whether a workplace discrimination? - Ali Mohamed, Ashgar Ali; Ahmad, Muhammad Hassan (Lexis Nexis Malaysia Sdn Bhd, 2021)
This article discusses on the issue of whether preventing a female Muslim employee from wearing a headscarf (hijab) at work amounts to discrimination and whether such refusal constitutes a valid ground for termination from employment. It is observed that there have been few incidents in Malaysia where women, particularly those working in customer service or the frontline such as the hotel receptionist, been prohibited from wearing headscarves at work, a violation of her constitutional rights to practice her religion